Oxidative production of xylonic acid using xylose in distillation stillage of cellulosic ethanol fermentation broth by Gluconobacter oxydans. (January 2017) - Zhang, Hongsen; Han, Xushen; Wei, Chengxiang; Bao, Jie
Graphical abstract: Highlights: Dry dilute acid pretreatment and biodetoxification are applied on corn stover biorefining. 75.22 g/L of xylonic acid is produced using xylose in cellulosic ethanol distillation stillage. 59.80 g/L of ethanol is also obtained before xylose fermentation. Significant reduction of wastewater generation and energy consumption are achieved. Aspen Plus modeling is conducted on the flowsheet simulation of the proposed process. Abstract: An oxidative production process of xylonic acid using xylose in distillation stillage of cellulosic ethanol fermentation broth was designed, experimentally investigated, and evaluated. Dry dilute acid pretreated and biodetoxified corn stover was simultaneously saccharified and fermented into 59.80 g/L of ethanol (no xylose utilization). 65.39 g/L of xylose was obtained in the distillation stillage without any concentrating step after ethanol was distillated. Then the xylose was completely converted into 66.42 g/L of xylonic acid by Gluconobacter oxydans . The rigorous Aspen Plus modeling shows that the wastewater generation and energy consumption was significantly reduced comparing to the previous xylonic acid production process using xylose in pretreatment liquid. This study provided a practical process option for xylonic acid production from lignocellulose feedstock with significant reduction of wastewater and energy consumption.